Modelling of abrasive waterjet milled footprints - Anwar, Saqib (2013)
Abrasive waterjet (AWJ) cutting is one of the most promising fast emerging non-traditional cutting technologies. It is highly competitive for machining difficult-to-cut materials like ceramics, composites and titanium alloys as compared to other nonconventional processes (e.g. laser, EDM) which are either technologically inappropriate or fail to be cost-effective. However, at the moment most of the usage of the AWJ machining lies in the area of the through cutting applications and to perform controlled depth cutting (milling) is still at craftsmanship level. This is due to the facts that: (i) AWJ machining is based on employing a jet plume as a "soft body" tool, the footprint of which not only depends on the jet energy parameters (e.g. pressure, abrasive mass flow rate, etc) but also on the jet kinematic parameters (e.g. jet traverse speed) which make controlling of the jet penetration depth very difficult; (ii) there is absence of the appropriate and reliable models that can simulate and predict the AWJ milled footprints and this is one of the major obstructions constraining the use of the AWJ milling applications.